The Development Inquiry Learning Model Oriented Life Skills through the Application of Simple Scientific Method Skill (S2ms) - Wicaksana, Ervan Johan (Proceeding of International Conference on Teacher Training and Education, 2016)
Paradigm in education must be shifted from the old paradigm that refers to teoritist science into a novel paradigm that is applied science. To change the paradigm above, the science lesson is certainly necessary for the development and its learning model learning devices in accordance with the new paradigm in education (applied science). It required a learning model that can meet the new paradigm and leads to a discovery or creation of a product, namely the inquiry learning model oriented life skills through the application of Simple Scientific Method Skill (S2MS). This type of research is the development of research using a model of Dick and Carrey performed on the stage of development and dissemination. The trial is limited to vocational students in Ngawi East Java, Indonesia were divided by 2 groups of classes, namely the control class and experimental class. Data collection methods include validation of inquiry learning model (syllabus, lesson plans, teaching materials, worksheets, and assessment), observation, test evaluation of learning outcomes, student questionnaire responses. Data was analyzed using descriptive methods. The results showed that the group inquiry learning model oriented life skills through the simple scientific method skill (S2MS) proved effective in improving achievement in learning and creativity of students in learning science at vocational students in Ngawi East Java Indonesia. This is seen in the average value of science in the experimental class group was higher (80.25) than in group control class (70.20). Meanwhile, a group of student creativity aesthetically experimental class is higher (3.80) than the control class group (2.58).